4-Bromo-1-[2,6-dichloro-4-(trifluoromethyl)phenyl]-5-(4-methoxybenzylideneamino)-1H-pyrazole-3-carbonitrile - Zhiping Yang; Shuyan Li; Guohui Zhu (Acta Crystallographica Section E, 2008)
The title compound, C19H10BrCl2F3N4O, is an imine with an overall Y shape. The dihedral angles between the pyrazole ring and the methoxy- and trifluoromethyl-substituted benzene ring planes are 88.4 (2) and 65.8 (2)°, respectively.